(untitled) (Collection of scientific works «Modern structures of metal and wood», 2019)
Recently, in the practice of constructing large-span spatial coatings, shallow mesh domes have been used more often than others. Such designs make it possible to form a smaller building volume, but their work under the influence of loads is much more complicated. And now the problems of calculating the stability of such domes are not sufficiently solved. The main reason is the difference between the experimental results and the performed calculations. The actual shape and position of the nodes of the mesh dome, as well as its actual stress-strain state during exploitation, differ from the state performed by the project. Accumulated deviations of the surface geometry of the dome during installation, manufacturing defects significantly change the ideal design scheme, which was used in the calculations, and increase the probability of loss of stability. The stability of shallow metal single-belt mesh domes with initial shape imperfections obtained in the process of erection of the structures is considered. The mesh dome was replaced with a continuous one and its nonaxisymmetric deformation with loss of stability from bifurcation loads was analyzed. The classification of the initial imperfections obtained by the structure during construction and mounting and the deviations of the loads applied to the structure is given. It is shown that the greatest influence on the loss of stability of a shallow spherical dome has imperfections in the shape of the middle surface. The approaches that lead to the convergence of discrepancies between the results of experimental critical loads of stability loss and theoretical are determined. In calculating stability, it is most important to take account of the initial imperfections of the form and the nonaxisymmetric deformation of the spherical dome, taking into account imperfections. For engineering calculations, the stability loss of shallow mesh domes is obtained by a dependence that allows you to adjust the critical load to take account the amplitude of the measured initial imperfections of the constructed structure. For the purpose of further research, it is important to investigate the effect of artificially created initial deviations of the mesh dome nodes from the ideal spherical shape in the direction opposite to the loss of stability, due to which a significant increase in the critical load can be achieved.